PENGARUH LEVERAGE, PERGANTIAN CEO DAN MOTIVASI PAJAK TERHADAP MANAJEMEN LABA - Chandra Yuliana (Fakultas Bisnis UKDW, 2011)
The purpose of this research is to test empirically the influence of leverage, turnover of CEO and tax motivation to earnings management, based on its discretionary accruals value. The sample of this research is listed manufacturing firms for the period 2004-2008 with 5 different subsectors. Statistical analysis method used in this research is logistic regression with binary logistic model. The result shows leverage does not have significant influence to earnings management while the turnovers of CEO and tax motivation have significant influence to earnings management.Keywords: Earnings Management, Leverage, CEO, Tax